Characterization of Different Cultivars of Mango Commercially Grown in Malda, India - Khara, S N; Thakur, Pran Krishna; Acharya, Pinaki; Dhua, R S (Journal of Postharvest Technology, 2016)
Fruits of eighteen mango varieties (Amrapali, Ashwina, Fazli, Gopalbhog, Khirshapati, Lakshmanbhog, Langra, Baishakhi Gooti, Rakhalbhog, Golapkhas, Ashudagi, Arajanma, Mallika, Krishanbhog, Michrikanta, Laxmibhog, Phunia and Brindabani) were collected from eight mango growing blocks of two Sub-divisions of Malda district. Both physico-chemical parameters were assessed at optimum ripening condition of fruits. Among the mango cultivars, the fruits of Fazli and Mallika were superior to others with regard to fruit weight and size. Phunia was the smallest in weight and size. The proportion of edible portion was highest in cv. Lakshmanbhog and was lowest in Michrikanta. In the present investigation, the maximum percent of total soluble solids was in cv. Mallika of 23.60 and minimum of 12.80 in cv. Lakshmanbhog. The total sugar, reducing sugar as well as non reducing sugar contents was maximum in cv. Mallika. The acidity of fruits varied from 0.15 –0.35%. The highest content of ascorbic acid was recorded in cv. Langra (56.34 mg / 100g). The highest TSS :Acid ratio was also recorded in the mango cvs. Mallika, Brindabani, Amrapali, Aswina, Gopalbhog, Rakhalbhog, Ashudagi and Kishanbhog. The highest and lowest amount of β-carotene was recorded in cv. Kishanbhog (17897 µg/100g) and cv. Brindabani (1089 µg/100g), respectively. The fruits of cv. Lakshmanbhog though contains lowest TSS:Acid as compared to Mallika (157.33), but have good attractive appearance, firm fruit, good keeping and transport quality, optimum size and shape, high fibreless edible proportion. The cv. Langra with high TSS : Acid (55.88) is one of the most popular cultivars of India. Thus, considering the fruit qualities, it was observed that some of the lesser known varieties viz. Michrikanta, Phunia, Ashudagi, Arajanma etc. have great potential for commercial exploitation. Also, regular bearing cultivar ‘Laxhmanbhog’ having good fruit quality and attractive colour could be a potent variety for export from the state.